Hyperoxia may be related to delayed cerebral ischemia and poor outcome after subarachnoid haemorrhage. Issue 12 (23rd May 2014) - Jeon, Sang-Beom; Choi, H Alex; Badjatia, Neeraj; Schmidt, J Michael; Lantigua, Hector; Claassen, Jan; Connolly, E Sander; Mayer, Stephan A; Lee, Kiwon
Abstract : Objective: To determine the association between exposure to hyperoxia and the risk of delayed cerebral ischaemia (DCI) after subarachnoid haemorrhage (SAH). Methods: We analysed data from a single centre, prospective, observational cohort database. Patient inclusion criteria were age ≥18 years, aneurysmal SAH, endotracheal intubation with mechanical ventilation, and arterial partial pressure of oxygen (PaO2 ) measurements. Hyperoxia was defined as the highest quartile of an area under the curve of PaO2, until the development of DCI (PaO2 ≥173 mm Hg). Poor outcome was defined as modified Rankin Scale 4–6 at 3 months after SAH. Results: Of 252 patients, there were no differences in baseline characteristics between the hyperoxia and control group. Ninety-seven (38.5%) patients developed DCI. The hyperoxia group had a higher incidence of DCI (p<0.001) and poor outcome (p=0.087). After adjusting for modified Fisher scale, rebleeding, global cerebral oedema, intracranial pressure crisis, pneumonia and sepsis, hyperoxia was independently associated with DCI (OR, 3.16; 95% CI 1.69 to 5.92; p<0.001). After adjusting for age, Hunt–Hess grade, aneurysm size, Acute Physiology and Chronic Health Evaluation II score, rebleeding, pneumonia and sepsis, hyperoxia was independently associated with poor outcome (OR, 2.30; 95% CI 1.03 to 5.12; p=0.042). Conclusions: In SAH patients, exposure to hyperoxia was associated with DCI. Our findings suggest that exposure to excess oxygen after SAH may represent a modifiable factor for morbidity and mortality in this population.